Modeling and experimental analysis of protein matrix solidification in cooling dies during high-moisture extrusion - Högg, Elisabeth; Horneber, Tobias; Rauh, Cornelia (Frontiers in Food Science and Technology, 2025)
IntroductionHigh-moisture extrusion (HME) has become a key method in the food industry for texturizing plant-based proteins to create high-moisture meat analogues (HMMAs) with meat-like textures. Despite its importance, the texturization process within the cooling die of the extruder remains not fully understood. This study aims to bridge this knowledge gap by combining experimental and numerical methods to analyze protein matrix solidification.MethodsIn-situ measurements, including temperature, pressure, velocity, and flow profiles, were conducted for various HME setups and die geometries. Numerical simulations based on the finite volume method incorporated thermophysical material properties from previous research to predict flow dynamics and structural changes. An inverse modeling approach was used to estimate unmeasurable parameters, and experimental validation included textural analysis, such as slice shear force and tensile strength.ResultsThe experimental and numerical studies showed strong agreement, validating the numerical model’s accuracy in simulating cooling die processes. Flow profiles visualized experimentally and numerically highlighted the correlation between structuring coefficients derived from kinematic variables and textural analysis results. Key findings indicated that cooling die geometries and process conditions significantly influence protein matrix solidification and the resulting texture of HMMAs.DiscussionThis study provides novel insights into the dynamics within cooling dies and establishes a robust framework for optimizing HME processes to enhance the textural quality of meat analogues. The validated numerical model enables future studies to explore diverse geometries and process conditions, contributing to advancements in plant-based protein texturization.